Repetitive transcranial magnetic stimulation for psychiatric symptoms in long-term hospitalized veterans with schizophrenia: A randomized double-blind controlled trial - Su, Xiuru; Zhao, Long; Shang, Yujie; Chen, Yingnan; Liu, Xiaowen; Wang, Xuan; Xiu, Meihong; Yu, Huijing; Liu, Lijun (Frontiers in Psychiatry, 2022)
Multiple lines of evidence demonstrate that high-frequency (HF) repetitive transcranial magnetic stimulation (rTMS) may improve clinical outcomes in patients with schizophrenia (SCZ). However, there is no research data on the efficacy of HF-rTMS on the psychiatric symptoms in veterans with SCZ. Herein, the present study aimed to investigate whether neuronavigated HF-rTMS was beneficial in alleviating the clinical symptoms in veterans with SCZ. Forty-seven veterans with treatment-resistant SCZ were randomly allocated to receive neuronavigated 10Hz rTMS (n=27) or sham stimulation (n=20) over left DLPFC for 4 consecutive weeks. Symptoms were assessed by using the Positive and Negative Syndrome Scale at baseline and at the end of week 4. We also collected easily available routine biochemical markers including blood sugar, lipid profiles, hormone and blood cell counts, considering that these markers may potentially be used to predict the outcomes of rTMS treatment. We found that there was a significant interaction effect of time and group on the positive symptoms. Compared with sham group, the positive factor score of veterans with SCZ was significantly decreased after treatment in real rTMS group. Interestingly, the improvement of positive symptoms from baseline to 4-week follow-up was significantly associated with the whole white blood cells (WBC) counts at baseline in the real rTMS group and baseline WBC counts were predictive for the symptom improvement after rTMS treatment. Our findings indicate that add-on neuronavigated 10Hz rTMS is beneficial on clinical symptoms in veterans with treatment-resistant SCZ. In addition, the baseline WBC counts were predictive for the outcomes after treatment. Key words: Schizophrenia; rTMS; Randomized controlled trial; Clinical outcome Trial Registration: ClinicalTrials.gov; identifier: NCT03774927